Non-Small Cell Lung Cancer (NSCLC): An Update (TAJ: Journal of Teachers Association, 2009)
Non-Small Cell lung Cancer can be treated with survival benefit providing better quality of life byapplying new chemotherapeutic dosing schemes. Though Surgery and Radiotherapy providegood results in non small cell lung cancer, most of the patients turn up to doctors in advancedstages where these facilities can not be offered properly. Combination chemotherapy withcarboplatin or cisplatin with Taxotere and Gemcirabine is now a better option. Chemotherapywith carboplatin, Gemcirabine, Taxotere and Novelbine is also a better dosing schemes.doi: 10.3329/taj.v15i2.3923TAJ December 2002; Vol.15(2): 115-118